Pemberdayaan Perempuan Melalui Gerakan PKK di Indonesia - Muktiono, Arif (Universitas Islam Indragiri, 2024)
Women's powerlessness does not only come from other people but also from themselves, where many women feel unworthy and unable to try new things. In writing this scientific work, the author uses a library research method in which the source of literature comes from books, archival documents, newspapers and journals that have been published first. The formulation of the problem is (1) What is meant by the PKK movement and its scope, (2) PKK's efforts in empowering women, especially villages in Indonesia, (3) Challenges in empowering women in Indonesia, (4) The role of village governments in empowering women. And the conclusions are (1) PKK is a movement that aims to empower women. PKK is a community development movement that originated from a household economy seminar held in Bogor in 1975 by producing 10 formulations in terms of family life, (2) PKK's efforts in empowering women, especially in villages, are by conducting (a) job skills training, (b) conducting training on financial services and microcredit, (c) providing work information focused on women's needs, (d) optimizing technology and communication information in the women's business chain, (e) collaborating with the private sector to provide work assistance and employment for women, (3) the challenges faced in empowering women are (a) lack of willingness from the women themselves, (b) lack of understanding from the women themselves (c) many women are still not literate in education and think women only sit at home taking care of family and children, (d) there is still a gender gap in the territory of Indonesia, (e) limited access to education and training, (f) lack of interest from women in developing opportunities in business from the government. (4) The role of the village government in empowering women is (a) increasing the number of women in terms of economic or employment activities, (b) increasing the number of women in making decisions in government, (c) targeting 30% representation of women in legislative elections, (d) increasing literacy rates through various programs including illiteracy or literacy education programs, (e) improving the quality of health services for mothers and children and providing education and. Socialization to pregnant women and prospective parents to use qualified birth attendants.